EFEKTIVITAS KONSELING KELOMPOK UNTUK MENINGKATKAN KETERBUKAAN DIRI SISWA KELAS VIII SMP NEGERI 1 PANGKAH KABUPATEN TEGAL - Pandhu Satrio Aliyhayyu Aksha (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2021)
Self disclosure is one of the important things that students must have because self- disclosure can encourage students to develop themselves, achieve, and have a good friendship environment. However, not many students have good self-disclosure, especially in class VIII of SMP Negeri 1 Pangkah. This problem can be overcome by providing group counseling to students who have self-disclosure problems. This study aims to determine the effectiveness of group counseling in increasing self-disclosure in class VIII of SMP Negeri 1 Pangkah. This type of research is a quasi-experimental research design in the form of one-group pretest-postest. The population studied was all grade VIII students of SMP Negeri 1 Pangkah with a research sample of 8 students of class VIII who had low to moderate levels of self-disclosure. The data were collected by means of pre-test and post-test using a scale of self-disclosure, interviews, and observations. The results showed that there was an increase in student self-